Strategi Komunikasi 92. 9 Fm Solo Radio Dalam Mendapatkan Perhatian Pendengar (Studi Deskripitif Kualitatif Terhadap Strategi Komunikasi Solo Radio Dalam Mendapatkan Perhatian Pendengar Dalam Program Acara Manahan) - Rozaq, Frayuda Ukivia; , Agus Triyono, M.Si (2017)
The development of radio broadcasting in the city of Solo from year to year shows significant growth. Solo radio development in terms of both quality and quantity leads to competition between the radio in order to survive and thrive. Listener as a target broadcasting constantly searching for radio programs that fit their needs in terms of both entertainment and information. Solo Radio as a radio station based in the city of Solo was also trying to survive and evolve the existing competition. Manahan Solo Radio programs were broadcast programs were the mainstay of the Solo Radio to get the listener's attention. This study aims to determine what communication strategy undertaken by Manahan Solo Radio program in getting the attention of the listener. This research was descriptive qualitative research that describes the communication strategy Manahan Solo Radio program in getting the attention of the listener. Analysis of experimental data using the pes of information ollection, data reduction, presentation and conclusion or verification. The study founded that the communication strategy Radio Solo Radio Solo program Manahan include (1) identifying the target of communication by adopting programs earlier and with trying to determine the condition of public audience Solo especially teenagers who were very intense on the development of information, it was precisely Solo Radio which has characteristics program with the theme of providing information and entertainment hot to the public, (2) to develop communication messages, were always trying to display messages or themes that were crowded in the audience so that the message was able to arouse the attention of the listener, and (3) establish methods consists of preparing the theme was the best, prepare for the best material, and prepare the ability or competence broadcasters.keywords: communication strategy, program Manahan, Solo Radio